A bifunctional salvage pathway for two distinct S‐adenosylmethionine by‐products that is widespread in bacteria, including pathogenic Escherichia coli. Issue 5 (20th February 2020) - North, Justin A.; Wildenthal, John A.; Erb, Tobias J.; Evans, Bradley S.; Byerly, Kathryn M.; Gerlt, John A.; Tabita, Fred R.
Abstract: S‐adenosyl‐l ‐methionine (SAM) is a necessary cosubstrate for numerous essential enzymatic reactions including protein and nucleotide methylations, secondary metabolite synthesis and radical‐mediated processes. Radical SAM enzymes produce 5ʹ‐deoxyadenosine, and SAM‐dependent enzymes for polyamine, neurotransmitter and quorum sensing compound synthesis produce 5ʹ‐methylthioadenosine as by‐products. Both are inhibitory and must be addressed by all cells. This work establishes a bifunctional oxygen‐independent salvage pathway for 5ʹ‐deoxyadenosine and 5ʹ‐methylthioadenosine in both Rhodospirillum rubrum and Extraintestinal Pathogenic Escherichia coli . Homologous genes for this pathway are widespread in bacteria, notably pathogenic strains within several families. A phosphorylase ( Rhodospirillum rubrum ) or separate nucleoside and kinase ( Escherichia coli ) followed by an isomerase and aldolase sequentially function to salvage these two wasteful and inhibitory compounds into adenine, dihydroxyacetone phosphate and acetaldehyde or (2‐methylthio)acetaldehyde during both aerobic and anaerobic growth. Both SAM by‐products are metabolized with equal affinity during aerobic and anaerobic growth conditions, suggesting that the dual‐purpose salvage pathway plays a central role in numerous environments, notably the human body during infection. Our newly discovered bifunctional oxygen‐independent pathway, widespread in bacteria, salvages at least two by‐products of SAM‐dependent enzymes for carbon and sulfur salvage, contributing to cell growth. Abstract : The cofactor S‐adenosyl‐l ‐methionine (SAM) plays an essential role in nucleotide methylation, polyamine formation and radical SAM enzymes, during which distinct inhibitory by‐products are formed. This work defines a dual‐purpose pathway for two SAM by‐products, 5ʹ‐methylthioadenosine and 5ʹ‐deoxyadenosine, that is widespread in bacteria, including Extraintestinal Pathogenic Escherichia coli . This pathway results in precursor metabolites of nucleotides, central carbon metabolism and methionine to support cell growth. The pathway appears functional in multiple environments, notably during human infection.